Diagnostic Evaluation of Nontraumatic Chest Pain in Athletes. Issue 2 (March 2017) - Moran, Byron; Bryan, Sean; Farrar, Ted; Salud, Chris; Visser, Gary; Decuba, Raymond; Renelus, Deborah; Buckley, Tyler; Dressing, Michael; Peterkin, Nicholas; Coris, Eric
Abstract : This article is a clinically relevant review of the existing medical literature relating to the assessment and diagnostic evaluation for athletes complaining of nontraumatic chest pain. The literature was searched using the following databases for the years 1975 forward: Cochrane Database of Systematic Reviews; CINAHL; PubMed (MEDLINE); and SportDiscus. The general search used the keywords chest pain and athletes. The search was revised to include subject headings and subheadings, including chest pain and prevalence and athletes. Cross-referencing published articles from the databases searched discovered additional articles. No dissertations, theses, or meeting proceedings were reviewed. The authors discuss the scope of this complex problem and the diagnostic dilemma chest pain in athletes can provide. Next, the authors delve into the vast differential and attempt to simplify this process for the sports medicine physician by dividing potential etiologies into cardiac and noncardiac conditions. Life-threatening causes of chest pain in athletes may be cardiac or noncardiac in origin, which highlights the need for the sports medicine physician to consider pathology in multiple organ systems simultaneously. This article emphasizes the importance of ruling out immediately life threatening diagnoses, while acknowledging the most common causes of noncardiac chest pain in young athletes are benign. The authors propose a practical algorithm the sports medicine physician can use as a guide for the assessment and diagnostic work-up of the athlete with chest pain designed to help the physician arrive at the correct diagnosis in a clinically efficient and cost-effective manner.